REDESAIN PASAR SUBUH LOA JANAN ULU PENEKANAN PADA SIRKULASI RUANG - HS, Cisyulia Octavia; Rulia, Anna; Putra, Hatta Musthafa Adham; Dhuhur, Maulana Refindo; Palayukan, Evan Cristian (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
The existence of the Loa Janan Fajr Market is very important in the development of the city's economy, especially for residents around Loa Janan Ulu. However, this market is becoming less well-organized, especially in market circulation, such as a narrow visitor circulation area, then there is no loading and unloading area to inadequate facilities and infrastructure. The purpose of this discussion is to make this market redesign even better, especially for circulation. The author makes observations about anything that can solve this. By surveying directly in the field and collecting data on what things need to be redesigned, the authors get a solution regarding the standardization of the people's market so that this market becomes comfortable, organized and safe when visiting this market.